Ultrathin halogen-free flame-retardant polypropylene material and preparation method thereof
Patent Information
- Application Number
- CN202611264420.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-09-22
AI Technical Summary
[0008]本发明技术方案针对现有技术解决方案过于单一的技术问题,提供了显著不同于现有技术的解决方案,主要提供了一种超薄无卤阻燃聚丙烯材料及其制备方法和应用,用以解决上述背景技术中提出的现有聚丙烯材料在超薄厚度下难以稳定达到UL94 V-0阻燃等级、阻燃剂添加量大导致力学性能劣化、阻燃剂易析出及与基体相容性差的技术问题
(1)本发明通过构建三聚氰胺聚磷酸盐、磷酸酯齐聚物、硅系阻燃剂、纳米蒙脱土四元协效体系,并采用阻燃剂粉体直接插层剥离蒙脱土的纳米复合工艺,在0.3~0.6mm超薄制品厚度下实现了UL9 4 V-0等级的稳定通过。对比例五表明,现有P-N-Si三元体系在0.5mm厚度下总余焰时间高达99s且全部引燃脱脂棉,无法达到V-0;而本发明实施例总余焰时间仅21~34s,且无引燃棉现象,阻燃效率提升达70%以上,解决了超薄聚丙烯材料难以达到V-0等级的技术难题。
Smart Images

Figure CN122790338A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flame-retardant polypropylene materials technology, specifically to an ultra-thin halogen-free flame-retardant polypropylene material and its preparation method. Background Technology
[0002] Polypropylene (PP) materials are widely used in packaging, electronics, new energy vehicles, and building materials due to their excellent properties such as light weight, insulation, chemical resistance, and ease of processing. However, PP itself is a flammable material with a limiting oxygen index (LOI) of only about 18%, and it exhibits severe dripping during combustion, easily igniting surrounding combustibles and posing significant safety hazards. Therefore, flame-retardant modification of PP has become a key technical means to expand its application range. Especially for ultra-thin products with a thickness ≤0.5mm (such as films and sheets), conventional flame-retardant modified PP materials still cannot meet stringent flame-retardant safety standards (such as UL94 V-0 rating), which places higher demands on the selection, compounding, and dispersion techniques of flame retardants.
[0003] Currently, the mainstream approach to improving the flame retardant properties of polypropylene is to add halogen-free flame retardants. Among them, phosphorus-nitrogen intumescent flame retardants (IFR) are considered one of the most promising directions for the development of halogen-free flame-retardant PP due to their advantages such as high flame retardant efficiency, low smoke, non-toxicity, and no corrosive gas release. For example, patent CN121249055A discloses a high-filling, aging-resistant flame-retardant polypropylene film. By adding halogen-free intumescent flame retardants and anti-dripping agents in masterbatch form, it achieves V-0 rating for PP films with thicknesses of 0.43mm and 0.25mm. However, the amount of halogen-free intumescent flame retardant masterbatch added is as high as 53.3-60%, and the excessively high total flame retardant filler content has a certain impact on the mechanical properties and appearance of the film. Patent CN120059348A discloses a flame-retardant insulating film, which includes a polypropylene resin matrix and a halogen-free intumescent flame retardant. The polypropylene resin matrix accounts for 47%-60% of the weight of the flame-retardant insulating film, but the flame retardant has poor dispersion, appearance defects, and performance degradation after aging.
[0004] However, existing technologies still have the following shortcomings: 1. With an extremely thin cross-section of 0.5mm, conventional flame retardant systems are prone to problems such as severe dripping, long afterflame time, and inability to achieve UL94 V-0 rating.
[0005] 2. Flame retardants have poor compatibility with PP matrix. Adding a high proportion of flame retardants will lead to a significant decrease in the toughness and impact strength of the material, making the product brittle and affecting its actual use.
[0006] 3. High filler systems lead to poor melt flowability, which can easily result in unstable extrusion, incomplete injection molding, rough surfaces, and even flame retardant precipitation and blooming.
[0007] 4. Some high-performance flame retardant systems are expensive and lack aging and weather resistance, making them difficult to use stably for a long time. Summary of the Invention
[0008] This invention addresses the problem of overly simplistic solutions in existing technologies by providing a significantly different approach. It primarily offers an ultrathin halogen-free flame-retardant polypropylene material, its preparation method, and its applications. This solution addresses the technical problems mentioned in the background section, such as the difficulty in consistently achieving the UL94 V-0 flame retardant rating in ultrathin polypropylene materials, the degradation of mechanical properties due to excessive flame retardant addition, the easy precipitation of flame retardants, and poor compatibility with the matrix.
[0009] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: An ultrathin halogen-free flame-retardant polypropylene material comprises the following raw materials in parts by weight: 60-70 parts of polypropylene resin; 28-38 parts of modified intumescent composite halogen-free flame retardant; 3-8 parts compatibilizer; Anti-dripping agent 0.3–1.0 parts; Antioxidant 0.2–0.5 parts; Lubricant 0.3 to 0.8 parts.
[0010] Furthermore, the polypropylene (PP) resin is a blend of homopolymer PP and copolymer PP, wherein the mass fraction of homopolymer PP is 35 to 50 parts and the mass fraction of copolymer PP is 10 to 35 parts.
[0011] The melt flow index of the polypropylene resin is 8-12 g / 10 min.
[0012] Furthermore, the modified intumescent composite halogen-free flame retardant includes: Melamine polyphosphate (MPP) is used to provide nitrogen-phosphorus expansion as the main flame retardant effect, with a particle size D50 of 3-5 μm; Phosphate ester oligomers are used to promote char formation and improve flame retardant efficiency, with a particle size D50 of 3-5 μm. Silicon-based flame retardants are used to improve the density of the char layer and enhance its anti-dripping properties. Nano-montmorillonite is used to form a dense physical barrier layer, improving the heat barrier properties of materials.
[0013] The phosphate oligomer is a cyclic phosphate oligomer, such as bis(4-aminophenyl)-phenyl phosphate (BAPP). The phosphate oligomer can also be bisphenol A bisphosphate or resorcinol phosphate oligomer.
[0014] The silicon-based flame retardant can be polysiloxane microspheres.
[0015] The total amount of the modified intumescent composite halogen-free flame retardant is 28–38 parts, of which melamine polyphosphate is 10–20 parts, phosphate oligomer is 6–14 parts, and silicone flame retardant is [missing information]. 1-2 parts, nano-montmorillonite 0.1-2 parts.
[0016] Furthermore, the preparation method of the modified intumescent composite halogen-free flame retardant includes the following steps: S1. Modification of montmorillonite: Sodium-based montmorillonite was vacuum dried at 110°C for 3 hours to remove adsorbed water. Then, the montmorillonite was surface activated with KH-550 (silane coupling agent) ethanol solution. After high-speed stirring for 30 minutes, it was dried for later use to obtain modified montmorillonite. S2. Premixed compound: Melamine polyphosphate, phosphate oligomer and silicone flame retardant are premixed evenly according to the weight parts, and then put into a high-speed mixer. The temperature is controlled at 85℃ and the speed is 800rpm. At the same time, modified montmorillonite is added in batches. S3, Intercalation and Delamination: The materials mixed in S2 are subjected to closed kneading treatment at a temperature of 110℃ for 25-35 minutes. By utilizing high-speed shearing and the intercalation effect of silane coupling agent, the interlayer structure of montmorillonite is opened up by flame retardant molecules, achieving single-layer nano-delamination. S4. Cooling and pulverizing: After cooling, the material is pulverized by airflow through a 300-mesh sieve to obtain flame retardant-nano montmorillonite composite powder, which is the modified intumescent composite halogen-free flame retardant.
[0017] In the modified intumescent composite halogen-free flame retardant, melamine polyphosphate, phosphate oligomers, and silicon-based flame retardants serve as flame-retardant active components. Through intercalation, they promote the exfoliation of montmorillonite sheets, allowing the flame-retardant active components to be loaded between the montmorillonite nanosheets, thereby forming a composite flame-retardant structure with synergistic effects of char formation and nano-barrier properties. Compared to the traditional method of preparing polymer / montmorillonite masterbatches using polymers as intercalating agents and then blending them with flame retardants, this invention uses the flame retardant mixture directly as an intercalating agent, allowing flame retardant molecules to be uniformly loaded onto the surface of the montmorillonite nanosheets, fundamentally changing the form and dispersion state of montmorillonite in the composite material.
[0018] Furthermore, the compatibilizer includes: Glycidyl methacrylate grafted PP (GMA-g-PP) is used to improve the compatibility of flame retardants with PP; Silane coupling agents, such as KH-550, can be used as surface-modified flame retardants to prevent agglomeration. Dispersants such as ethylene bis-stearamide (EBS) can be used to improve powder dispersion and film surface.
[0019] The total amount of compatibilizer is 3 to 8 parts, of which GMA-g-PP accounts for 60 to 70 wt%, silane coupling agent accounts for 12 to 20 wt%, and dispersant accounts for 15 to 25 wt%.
[0020] In the above compound system, the epoxy groups in glycidyl methacrylate grafted PP can chemically react with the polar groups on the surface of the flame retardant. At the same time, its PP backbone has good compatibility with the polypropylene matrix, thus playing a bridging role and improving the interfacial bonding ability between the flame retardant powder and the polypropylene matrix. The silane coupling agent KH-550 modifies the surface of the flame retardant particles, reduces their surface energy, and prevents particle agglomeration. Ethylene bis-stearamide (EBS) acts as a dispersant, further promoting the uniform dispersion of powder in the resin. The three work synergistically to improve the surface quality of the film.
[0021] Furthermore, the anti-dripping agent includes: Polytetrafluoroethylene (PTFE) micro powder is used for anti-dripping and suppression of molten droplets; Pentaerythritol can be used as a char-forming agent to promote a dense char layer.
[0022] The total amount of anti-dripping agent is 0.3 to 1.0 parts, of which PTFE micro powder accounts for 40 to 60 wt% and pentaerythritol accounts for 40 to 60 wt%.
[0023] The char-forming agent may also be at least one of sorbitol, xylitol, melamine polyol, and starch polyol, which are polyhydroxy carbon sources that are heated, dehydrated, and carbonized to form a dense carbon layer; the amount added can be adjusted within the range of ±5% to 10% according to the difference in char-forming efficiency.
[0024] Furthermore, antioxidants include: Antioxidant 1010 is used for primary antioxidant protection and prevention of thermo-oxidative aging. Antioxidant 168 is used as an auxiliary antioxidant and synergistic stabilizer. Polysiloxane-coated nano zinc oxide is used for UV absorption, flame retardant synergy, and anti-aging.
[0025] The total amount of antioxidants is 0.2 to 0.5 parts, of which antioxidant 1010 accounts for 35 to 50 wt%, antioxidant 168 accounts for 35 to 50 wt%, and polysiloxane-coated nano zinc oxide accounts for 10 to 20 wt%. Compared to conventional nano zinc oxide, polysiloxane-coated nano zinc oxide is less prone to agglomeration and has better compatibility with PP. At the same time, the polysiloxane shell can participate in char formation during combustion, playing a synergistic role in flame retardancy.
[0026] Furthermore, calcium stearate can be used as a lubricant to improve processing fluidity.
[0027] After melting during processing, calcium stearate migrates to the resin-equipment metal interface, reducing the frictional resistance between the melt and the screw and die, improving the melt flowability of high-filled flame retardant, avoiding extrusion fouling and die surface blooming, and helping to improve the surface smoothness of the cast film.
[0028] The preparation method of the above-mentioned ultrathin halogen-free flame-retardant polypropylene material includes the following steps: S1. Raw material pretreatment: Each raw material is dried to ensure that the moisture content is <0.05%; S2. High-speed mixing: Add the ingredients to the high-speed mixer according to the ratio, control the speed at 1000 rpm, and stir for 5 minutes to achieve uniform mixing; S3. Twin-screw granulation: The length-to-diameter ratio of the twin screw is L / D=48:1, and the barrel temperature is controlled at 175~190℃ (barrel), the rotation speed is 250~300rpm, and the feeding speed is 120~140kg / h; then water-cooled pellets are cut and dried at 80℃ to obtain flame-retardant PP masterbatch. S4. Melt Plasticization and Molding: The flame-retardant PP masterbatch obtained in step S3 is melt plasticized by an extruder and then melt-molded to obtain an ultra-thin halogen-free flame-retardant polypropylene material.
[0029] In step S1, different substances are dried separately in batches, and the drying time varies for different materials. PP resin is vacuum dried at 80℃ for 2 hours; various flame retardant powders (MPP / BAPP / silicon microspheres / modified montmorillonite) are vacuum dried at 80℃ for 3.5-4 hours; and additives (composite agents, antioxidants, PTFE, calcium stearate) are dried at 80℃ for 2 hours.
[0030] In step S2, the order of feeding is as follows: first add PP resin and premix at high speed for 1 minute; Then, add the compatibilizer (GMA-g-PP, KH550, EBS) in batches and mix for 1.5 minutes until the resin melts and wets the compatibilizer. Then, slowly add the flame-retardant composite powder, PTFE, and charring agent and mix for 1.5 minutes. Finally, add the antioxidant and calcium stearate and mix for another 1 minute to complete the mixing process.
[0031] In step S3, the cooling water temperature is 10–40°C; the drying time is 10–20 seconds; and the qualified drying standard is a moisture content of less than 0.1%.
[0032] In step S4, the extrusion temperature of the extruder is 200-220°C.
[0033] Preferably, in step S4, the molding process employs a casting molding process, specifically: the molten and plasticized material is extruded through a T-shaped casting die (i.e., molding die), cast onto a cooling roller for rapid cooling and molding, and then subjected to traction, thickness measurement, edge trimming, and winding to obtain an ultra-thin halogen-free flame-retardant polypropylene film product. The casting film forming process parameters are: die temperature 210–225℃, cooling roller temperature 25–50℃, and traction speed 5–20 m / min.
[0034] In step S4, the T-die head is equipped with a precision adjustable die lip and an online thickness gauge (β-ray thickness measurement). By pre-adjusting the die lip gap and combining it with real-time feedback from the online thickness gauge, the thickness of the film is precisely controlled. For example, when the target thickness is 0.5 mm, the die lip gap can be pre-adjusted to 0.52 mm. Combined with the subsequent traction stretching ratio, a film product with a thickness of 0.5 mm is finally obtained.
[0035] In this invention, the shear ratio L / D of the twin-screw mixing section is 48:1. Compared to the conventional 32:1 to 40:1 configuration, the longer screw combination provides sufficient shearing and dispersion time for the flame retardant to disperse in the matrix and for the nano-exfoliation of montmorillonite. If the shearing is too strong (e.g., the aspect ratio is too large or the shear blocks are too dense), the flame retardant is prone to decomposition due to excessive heating; if the shearing is insufficient (e.g., the aspect ratio is too small), it is difficult for montmorillonite to achieve nano-exfoliation, resulting in uneven dispersion and poor compatibility of the flame retardant. Therefore, the L / D of 48:1 in this invention, combined with a relatively low barrel temperature of 175 to 190°C, can ensure sufficient dispersion while avoiding thermal decomposition of the flame retardant.
[0036] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention achieves stable UL94 V-0 rating at ultra-thin product thicknesses of 0.3–0.6 mm by constructing a quaternary synergistic system of melamine polyphosphate, phosphate ester oligomer, silicon-based flame retardant, and nano-montmorillonite, and by employing a nanocomposite process of direct intercalation and exfoliation of montmorillonite with flame retardant powder. Comparative Example 5 shows that the existing PN-Si ternary system has a total afterflame time as high as 99 s at a thickness of 0.5 mm and completely ignites the degreased cotton, failing to achieve V-0; while the total afterflame time of the embodiment of this invention is only 21–34 s, and there is no cotton ignition phenomenon, with a flame retardant efficiency improvement of more than 70%, solving the technical problem that ultra-thin polypropylene materials are difficult to achieve V-0 rating.
[0037] (2) The total amount of the modified intumescent composite halogen-free flame retardant of the present invention is only 28 to 38 parts, which is much lower than the 53.3 to 60% addition amount in the prior art. It achieves high-efficiency flame retardancy under low filling conditions and avoids the deterioration of the mechanical properties of ultra-thin products.
[0038] (3) This invention uses an intercalation composite process to load flame-retardant active components between montmorillonite nanosheets, forming a four-fold synergistic mechanism of expansion into char, promotion of char formation, enhancement of char layer, and physical barrier. Comparative Example 2 shows that the total afterflame time without montmorillonite is 108s, and Comparative Example 6 shows that the total afterflame time without intercalation treatment of montmorillonite is 79s with drastic fluctuations; while Example 4, under the same formulation, has a total afterflame time of only 29s and all five samples passed. The above comparisons prove that montmorillonite must be intercalated and exfoliated to achieve nanoscale dispersion in order to exert its synergistic effect of physical barrier and char formation enhancement; conventional blending cannot achieve the same effect.
[0039] (4) This invention solves the processing problem of high-filling flame-retardant systems by introducing polysiloxane microspheres and the synergistic effect of the ternary compatibilizer system. Comparative Example 1 shows that the absence of polysiloxane microspheres results in serious processing failures such as frequent extrusion breakage and inability to form, proving that polysiloxane microspheres have both flame-retardant synergistic effect and processing lubrication function.
[0040] (5) The ultrathin halogen-free flame-retardant polypropylene material prepared by this invention has excellent processing stability and flame-retardant reproducibility. Examples 1 to 4 can stably pass V-0 (5 / 5) under different flame retardant ratios within a thickness range of 0.3 to 0.6 mm. The total afterflame time of the five samples is stable between 21 and 41 s, with small fluctuations within batches. In contrast, Comparative Example 3 (with a lower content of modified intumescent composite halogen-free flame retardant) and Comparative Example 6 (without intercalation treatment of montmorillonite) both showed drastic fluctuations with alternating pass / fail (Y / N) results, and could not stably reach the V-0 rating. The above comparison proves that the technical solution of this invention can only achieve a stable flame-retardant effect under specific component ranges and specific introduction methods, and has good process robustness and industrial production feasibility.
[0041] (6) The present invention breaks through the critical thickness barrier of the prior art disclosed in Comparative Example 5, which causes the flame retardant performance to suddenly fail when the thickness is reduced from 1.0 mm to 0.5 mm. Comparative Example 7 shows that the total afterflame time of the same formula is only 20s at a thickness of 0.8 mm and the V-0 margin is larger. Together with the 29s of 0.5 mm, it proves that the formula and process of the present invention still maintain sufficient flame retardant margin at ultra-thin critical thickness.
[0042] The present invention will be explained in detail below with reference to the accompanying drawings and specific embodiments. Attached Figure Description
[0043] Figure 1 This is a process flow diagram for preparing the ultrathin halogen-free flame-retardant polypropylene material of the present invention; Figure 2 This is a process flow diagram for preparing the modified intumescent composite halogen-free flame retardant of the present invention. Detailed Implementation
[0044] To facilitate understanding of the present invention, a more comprehensive description of the present invention will be given below with reference to the accompanying drawings, which illustrate several embodiments of the present invention. However, the present invention can be implemented in different forms and is not limited to the embodiments described in the text. Rather, these embodiments are provided to make the disclosure of the present invention more thorough and comprehensive.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0046] This embodiment and comparative example use film products as an example for illustration, but those skilled in the art will understand that the material is also applicable to other forms of products such as sheets and injection molded parts.
[0047] Example 1: An ultra-thin halogen-free flame-retardant polypropylene material, comprising the following parts by weight of raw materials: 45 parts of homopolymer polypropylene resin, 20 parts of copolymer polypropylene resin; 32 parts of modified intumescent composite halogen-free flame retardant; 5 parts of compatibilizer; 0.6 parts of anti-dripping agent; 0.3 parts of antioxidant; and 0.5 parts of lubricant.
[0048] The melt flow index of the polypropylene resin is 8-12 g / 10 min.
[0049] The modified intumescent composite halogen-free flame retardant includes: 20 parts of melamine polyphosphate (MPP) with a particle size D50 of 3-5 μm; 10 parts of bis(4-aminophenyl)-phenyl phosphate (BAPP) with a particle size D50 of 3-5 μm; 1 part of polysiloxane microspheres; and 1 part of nano-montmorillonite.
[0050] like Figure 2 As shown, the preparation method of the modified intumescent composite halogen-free flame retardant includes the following steps: S1. Modification of montmorillonite: Sodium-based montmorillonite was vacuum dried at 110°C for 3 hours to remove adsorbed water. Then, the montmorillonite was surface activated with KH-550 (silane coupling agent) ethanol solution. After high-speed stirring for 30 minutes, it was dried for later use to obtain modified montmorillonite. S2. Premixed compound: Melamine polyphosphate, phosphate oligomer and silicone flame retardant are premixed evenly according to the weight parts, and then put into a high-speed mixer. The temperature is controlled at 85℃ and the speed is 800rpm. At the same time, modified montmorillonite is added in batches. S3, Intercalation and Delamination: The materials mixed in S2 are subjected to closed kneading treatment at a kneading temperature of 110℃ for 30 minutes; by utilizing high-speed shearing and the intercalation effect of silane coupling agent, the interlayer structure of montmorillonite is opened up by flame retardant molecules, achieving single-sheet nano-delamination. S4. Cooling and pulverizing: After cooling, the material is pulverized by airflow through a 300-mesh sieve to obtain flame retardant-nano montmorillonite composite powder, which is the modified intumescent composite halogen-free flame retardant.
[0051] The compatibilizer includes: 3 parts of glycidyl methacrylate-grafted PP (GMA-g-PP), 1 part KH-550 (silane coupling agent); 1 part ethylene bis-stearamide (EBS).
[0052] The anti-dripping agent includes: 0.3 parts of polytetrafluoroethylene (PTFE) micro powder and 0.3 parts of pentaerythritol.
[0053] The antioxidants include: 0.13 parts of antioxidant 1010, 0.14 parts of antioxidant 168, and 0.03 parts of polysiloxane-coated nano zinc oxide.
[0054] The coating process of polysiloxane-coated nano zinc oxide specifically includes the following steps: S1. Disperse nano-ZnO powder in anhydrous ethanol and disperse at high speed to prepare a suspension; S2. Add methyl polysiloxane prepolymer and trace amounts of organotin catalyst (such as dibutyltin dilaurate), and stir the reaction at 65°C for 3 hours. S3. After centrifugation, vacuum drying at 80℃, and air jet pulverization, polysiloxane-coated nano zinc oxide is obtained.
[0055] Calcium stearate can be used as a lubricant.
[0056] like Figure 1 As shown, the preparation method of the above-mentioned ultrathin halogen-free flame-retardant polypropylene material includes the following steps: S1. Raw material pretreatment: PP resin is vacuum dried at 80℃ for 2 hours; various flame retardant powders (MPP / BAPP / silicon microspheres / modified montmorillonite) are vacuum dried at 80℃ for 4 hours; additives (composite agent, antioxidant, PTFE, calcium stearate) are dried at 80℃ for 2 hours to ensure the raw material moisture content is <0.05%. S2. High-speed mixing: First, add PP resin and premix at high speed for 1 minute; then add compatibilizer (GMA-g-PP, KH550, EBS) in batches and mix for 1.5 minutes until the resin melts and wets the compatibilizer; then slowly add modified intumescent composite halogen-free flame retardant, PTFE, and pentaerythritol and mix for 1.5 minutes; finally, add antioxidant and calcium stearate and mix for 1 minute to ensure the materials are well mixed. S3. Twin-screw granulation: The length-to-diameter ratio of the twin screw is L / D=48:1, and the barrel temperature is controlled at 175-190℃ (barrel), the rotation speed is 280rpm, and the feeding speed is 130kg / h; then it is water-cooled and pelletized in cooling water at 25℃, and dried at 80℃ to make the moisture content less than 0.1%, thus obtaining flame-retardant PP masterbatch; S4. Casting and Film Forming: The flame-retardant PP masterbatch obtained in step S3 is melted and plasticized in a single-screw extruder at an extrusion temperature of 210℃. It is then cast through a T-die onto a cooling roller for rapid cooling and forming. The die temperature is 220℃, and the cooling roller temperature is 30℃. The T-die is equipped with a precision adjustable die lip and an online thickness gauge (β-ray thickness measurement). The die lip gap is pre-adjusted to 0.52mm. After traction, thickness measurement, edge trimming, and winding, a traction speed of 10m / min is used to obtain a halogen-free flame-retardant polypropylene film product with a thickness of 0.5mm (this material is used in film form).
[0057] Example 2: The difference between this example and Example 1 is that: An ultrathin halogen-free flame-retardant polypropylene material comprises the following raw materials in parts by weight: 50 parts homopolymer polypropylene resin, 10 parts copolymer polypropylene resin; 38 parts modified intumescent composite halogen-free flame retardant; 3 parts compatibilizer; 1.0 part anti-dripping agent; 0.5 parts antioxidant; and 0.8 parts lubricant.
[0058] The modified intumescent composite halogen-free flame retardant includes: 20 parts of melamine polyphosphate (MPP) with a particle size D50 of 3-5 μm; 14 parts of bis(4-aminophenyl)-phenyl phosphate (BAPP) with a particle size D50 of 3-5 μm; 2 parts of polysiloxane microspheres; and 2 parts of nano-montmorillonite.
[0059] When preparing the modified intumescent composite halogen-free flame retardant, the mixing time for intercalation and delamination is 25 minutes.
[0060] The compatibilizer includes: 2 parts of glycidyl methacrylate-grafted PP (GMA-g-PP), 0.3 parts of KH-550 (silane coupling agent); 0.7 parts of ethylene bis-stearamide (EBS).
[0061] The anti-dripping agent includes: 0.6 parts of polytetrafluoroethylene (PTFE) micro powder and 0.4 parts of pentaerythritol.
[0062] The antioxidants include: 0.2 parts of antioxidant 1010, 0.2 parts of antioxidant 168, and 0.1 parts of polysiloxane-coated nano zinc oxide.
[0063] In the above-mentioned preparation method of ultrathin halogen-free flame-retardant polypropylene material: S1. Raw material pretreatment: Various flame-retardant powders (MPP / BAPP / silicon microspheres / modified montmorillonite) are vacuum dried at 80℃ for 3.5h; S3, Twin-screw granulation: The rotation speed is controlled at 250 rpm and the feeding speed is 120 kg / h; then it is water-cooled and pelletized in 40℃ cooling water. S4. Casting film: Extrusion temperature is 200℃; die head temperature is 210℃, cooling roller temperature is 25℃, die lip gap is pre-adjusted to 0.32mm; traction speed is 5m / min, to obtain a halogen-free flame-retardant polypropylene film product with a thickness of 0.3mm (this material is used in film form).
[0064] Everything else is the same as in Example 1.
[0065] Example 3: The difference between this example and Example 1 is that: An ultrathin halogen-free flame-retardant polypropylene material comprises the following raw materials in parts by weight: 35 parts homopolymer polypropylene resin, 35 parts copolymer polypropylene resin; 28 parts modified intumescent composite halogen-free flame retardant; 8 parts compatibilizer; 0.3 parts anti-dripping agent; 0.2 parts antioxidant; and 0.3 parts lubricant.
[0066] The modified intumescent composite halogen-free flame retardant includes: 15 parts of melamine polyphosphate (MPP) with a particle size D50 of 3-5 μm; 10 parts of bis(4-aminophenyl)-phenyl phosphate (BAPP) with a particle size D50 of 3-5 μm; 1 part of polysiloxane microspheres; and 2 parts of nano-montmorillonite.
[0067] When preparing the modified intumescent composite halogen-free flame retardant, the mixing time for intercalation and delamination is 35 minutes.
[0068] The compatibilizer includes: 5 parts of glycidyl methacrylate-grafted PP (GMA-g-PP), 1.5 parts of KH-550 (silane coupling agent); 1.5 parts of ethylene bis-stearamide (EBS).
[0069] The anti-dripping agent includes: 0.12 parts of polytetrafluoroethylene (PTFE) micro powder and 0.18 parts of pentaerythritol.
[0070] The antioxidants include: 0.1 parts of antioxidant 1010, 0.07 parts of antioxidant 168, and 0.03 parts of polysiloxane-coated nano zinc oxide.
[0071] In the above-mentioned preparation method of ultrathin halogen-free flame-retardant polypropylene material: S3, Twin-screw granulation: The rotation speed is controlled at 300 rpm and the feeding speed is 140 kg / h; then it is water-cooled and pelletized in 10℃ cooling water. S4. Casting film: The extrusion temperature is 220℃; the die temperature is 225℃; the cooling roller temperature is 50℃; the die lip gap is pre-adjusted to 0.62mm; the traction speed is 20m / min, resulting in a halogen-free flame-retardant polypropylene film product with a thickness of 0.6mm (this material is used in film form).
[0072] Everything else is the same as in Example 1.
[0073] Example 4: The difference between this example and Example 1 is that: An ultrathin halogen-free flame-retardant polypropylene material comprises the following raw materials in parts by weight: 40 parts homopolymer polypropylene resin, 25.5 parts copolymer polypropylene resin, 28 parts modified intumescent composite halogen-free flame retardant, 5 parts compatibilizer, 0.6 parts anti-dripping agent, 0.3 parts antioxidant, and 0.6 parts lubricant.
[0074] The modified intumescent composite halogen-free flame retardant includes: 15 parts melamine polyphosphate (MPP); 10 parts BAPP; 1 part polysiloxane microspheres; and 2 parts nano-montmorillonite.
[0075] Everything else is the same as in Example 1.
[0076] Comparative Example 1: The only difference from Example 4 is that the raw materials of the modified intumescent composite halogen-free flame retardant do not contain polysiloxane silicon spheres. Everything else is the same as Example 4.
[0077] Comparative Example 2: The only difference from Example 4 is that the raw materials of the modified intumescent composite halogen-free flame retardant do not contain montmorillonite. Everything else is the same as Example 4.
[0078] Comparative Example 3: The only difference from Example 4 is that 27 parts of modified intumescent composite halogen-free flame retardant were used; of which 15 parts were melamine polyphosphate (MPP); 10 parts were BAPP; 1 part were polysiloxane microspheres; and 1 part were nano-montmorillonite. All other components were the same as in Example 4.
[0079] Comparative Example 4: The only difference from Example 4 is that 40 parts of modified intumescent composite halogen-free flame retardant were used; of which 20 parts were melamine polyphosphate (MPP); 14 parts were BAPP; 3 parts were polysiloxane microspheres; and 3 parts were nano-montmorillonite. Everything else was the same as in Example 4.
[0080] Comparative Example 5: An ultra-thin halogen-free flame-retardant polypropylene material, comprising the following raw materials in parts by weight: 70 parts homopolymer polypropylene resin; 15 parts ammonium polyphosphate (APP); 10 parts melamine polyphosphate (MPP); 5 parts TDK (containing silicon charring agent); 5 parts compatibilizer (PP-g-MAH); 0.5 parts anti-dripping agent (PTFE); 0.3 parts antioxidant (1010 / 168 compound); and 0.5 parts lubricant (calcium stearate).
[0081] The raw materials do not contain BAPP, polysiloxane microspheres, or montmorillonite, and the flame retardant is added using conventional physical blending methods without intercalation or composite treatment. Other aspects are the same as in Example 4.
[0082] Comparative Example 6: The difference from Example 4 is that: Two parts of unmodified sodium-based montmorillonite were used; and the montmorillonite was not subjected to intercalation and exfoliation treatment, but was directly added together with other flame-retardant powders (MPP, BAPP, polysiloxane microspheres) in the high-speed mixing step of the membrane preparation method. Other procedures were the same as in Example 4.
[0083] Comparative Example 7: The difference from Example 4 is that: During the casting process, the gap between the T-shaped die lips was pre-adjusted to 0.83 mm, and the traction speed was adjusted to 8 m / min, resulting in a halogen-free flame-retardant polypropylene material with a thickness of 0.8 mm. Other procedures were the same as in Example 4.
[0084] The following is a comparative analysis of Example 4 and Comparative Examples 1-7: 1. Processing performance test During the preparation process, the processing performance was evaluated by observing the continuity of film formation. The test results are shown in Table 1: Table 1. Statistical table of processing performance of Example 4 and each comparative example.
[0085] As shown in Table 1: Examples 1 to 4 can all be produced continuously and stably on conventional casting equipment, with smooth and defect-free film surfaces. This indicates that within the formulation range of 60-70 parts of polypropylene resin and 28-38 parts of modified intumescent composite halogen-free flame retardant defined in this invention, the material system has excellent melt strength and processing fluidity, and can meet the requirements of industrial-scale mass production.
[0086] In Comparative Example 1, the absence of just one part of polysiloxane microspheres resulted in severe processing failures, including frequent extrusion breakage and difficulty in molding. This demonstrates that in the system of this invention, polysiloxane microspheres not only act as a silicon-based flame retardant synergist, but their microsphere morphology also plays a role in internal lubrication and dispersion promotion during processing.
[0087] In Comparative Example 4, when the total amount of flame retardant increased to 40 parts (exceeding the upper limit of 38 parts in this invention), even though montmorillonite underwent intercalation treatment, the system still could not be produced normally due to torque overload. This indicates that the range of 28 to 38 parts of flame retardant dosage is not arbitrarily chosen, but rather a critical upper limit of the processing window while ensuring flame retardant performance.
[0088] In Comparative Example 6, the same amount of montmorillonite, without intercalation and exfoliation treatment, was directly blended in the form of micron-sized agglomerates, leading to frequent screen blockage and strip breakage. The film surface was covered with white crystalline dots (flame retardant agglomerates), resulting in complete processing failure. In contrast, the intercalated montmorillonite in Example 4 achieved nanoscale dispersion, resulting in smooth processing. This comparison directly proves that the method of introducing montmorillonite (intercalation composite process) is as important as the montmorillonite itself. Simply adding raw montmorillonite powder not only does not improve flame retardancy but also severely degrades processing performance.
[0089] 2. Flame retardant performance test The vertical burning test method in the UL 94 standard for flammability testing of plastic materials was used, with five samples prepared for each type. Record: the afterflame time after each ignition; the total afterflame time of the five samples; whether molten drips were produced; and whether the drips ignited the absorbent cotton below. Determine whether the material meets the UL 94 V-0 rating. The conditions for a material to meet the UL 94 V-0 rating include: (1) The afterflame time of each sample after two ignitions shall not exceed 10s (the afterflame time after the first ignition shall be recorded as t1, and the afterflame time after the second ignition shall be recorded as t2). (2) The total afterflame time of the five samples shall not exceed 50s; (3) There was no phenomenon of burning drippings igniting the absorbent cotton; (4) No continuous burning phenomenon after the second ignition.
[0090] The test results are shown in Table 2.
[0091] Table 2. Flame retardant performance statistics of Example 4 and each comparative example. As shown in Table 2:
[0092] Comparative Example 2 (excluding montmorillonite) showed a total afterflame time as high as 108s at a thickness of 0.5mm, with all five samples igniting the absorbent cotton, indicating a nitrogen (N) flammability. However, Example 4, using the same amounts of MPP, BAPP, and silica microspheres, only added two parts of intercalated montmorillonite, resulting in a dramatic decrease in the total afterflame time to 29s, a reduction of 73%, and all five samples consistently passed V-0. These results indicate that the ternary system of MPP-BAPP-silica microspheres has a bottleneck in flame retardant efficiency at an ultra-thin cross-section of 0.5mm. The nano-physical barrier layer formed by the intercalation and exfoliation of montmorillonite, combined with the phosphorus-nitrogen-silicon expanded char system, forms a quadruple synergistic mechanism of expansion char formation, char promotion, char layer enhancement, and physical barrier, producing a flame retardant enhancement effect far exceeding linear superposition.
[0093] Comparative Example 3 (1 part montmorillonite) had a total afterflame time of 58 s, with only three out of five samples passing and two failing, making it impossible to reliably determine as V-0. In contrast, Example 4 (2 parts montmorillonite) had all five samples passing stably. Combined with Comparative Example 2 (0 parts montmorillonite, total afterflame time 108 s), it can be seen that the more montmorillonite added, the shorter the total afterflame time, from 0 to 2 parts.
[0094] Comparative Example 5 reproduced the PN-Si ternary intumescent flame retardant system disclosed in the prior art (a paper from Tianjin University of Science and Technology). This system could stably pass V-0 at a thickness of 1.0 mm, but at a thickness of 0.5 mm, the total afterflame time deteriorated to 99 s, and all five samples ignited the degreased cotton. This indicates that when the thickness decreases from 1.0 mm to 0.5 mm, the flame retardant performance undergoes an abrupt change from acceptable to severe failure, rather than a linear decay.
[0095] Comparative Example 7 uses the exact same formulation as Example 4, except that the thickness is increased from 0.5 mm to 0.8 mm, the total afterflame time is further reduced from 29 s to 20 s. This demonstrates that the formulation of the present invention itself has excellent flame-retardant properties, and it can still maintain sufficient afterflame time margin (29 s is far below the 50 s threshold) at a thickness of 0.5 mm, fully proving that the quaternary synergy and intercalation composite process of the present invention jointly overcome the ultrathin critical thickness limitation.
[0096] In Comparative Example 6, montmorillonite was directly blended without intercalation treatment. Although the formulation was exactly the same as in Example 4, the flame retardancy results of the five samples showed drastic fluctuations with alternating Y / N ratios because the montmorillonite was dispersed as micron-sized aggregates and could not form a nano-barrier layer. The total afterflame time was 79 s, and it could not stably pass V-0. This indicates that the nano-dispersion state of montmorillonite is a necessary condition for it to exert its flame retardant synergistic function. Simply adding montmorillonite as a filler to PP not only fails to achieve flame retardant enhancement, but also causes the aggregates to become stress defect points and combustion hotspots, resulting in a serious deterioration of flame retardant stability.
[0097] In summary, this invention achieves stable UL94 V-0 rating at ultra-thin thicknesses of 0.3–0.6 mm by constructing a quaternary synergistic flame-retardant system of melamine polyphosphate, phosphate ester oligomers, polysiloxane microspheres, and nano-montmorillonite, and employing a nanocomposite process of direct intercalation and exfoliation of montmorillonite with a flame retardant mixture. Furthermore, this invention addresses the problems of poor processing flowability, easy precipitation of flame retardants, and deterioration of mechanical properties in highly filled flame-retardant systems through the synergistic effect of the ternary compatible dispersion system of GMA-g-PP, KH-550, and EBS, and by utilizing an optimized processing window.
[0098] The present invention has been described by way of example in conjunction with the accompanying drawings. Obviously, the specific implementation of the present invention is not limited to the above-described manner. Any non-substantial improvement made by adopting the inventive concept and technical solution of the present invention, or the direct application of the inventive concept and technical solution of the present invention to other occasions without modification, shall be within the protection scope of the present invention.
Claims
1. An ultra-thin halogen-free flame-retardant polypropylene material, characterized in that: The raw materials include the following parts by weight: 60-70 parts of polypropylene resin; 28-38 parts of modified intumescent composite halogen-free flame retardant; 3-8 parts compatibilizer; Anti-dripping agent 0.3–1.0 parts; Antioxidant 0.2–0.5 parts; Lubricant 0.3–0.8 parts; The modified intumescent composite halogen-free flame retardant includes melamine polyphosphate, phosphate oligomers, silicon-based flame retardants, and nano-montmorillonite.
2. The ultra-thin halogen-free flame-retardant polypropylene material according to claim 1, characterized in that: The polypropylene resin is composed of homopolymer polypropylene and copolymer polypropylene, wherein the homopolymer polypropylene is 35-50 parts and the copolymer polypropylene is 10-35 parts. The melt flow index of the polypropylene resin is 8-12 g / 10 min.
3. The ultra-thin halogen-free flame-retardant polypropylene material according to claim 1, characterized in that: The modified intumescent composite halogen-free flame retardant comprises 10-20 parts of melamine polyphosphate, 6-14 parts of phosphate ester oligomer, 1-2 parts of silicon-based flame retardant, and 0.1-2 parts of nano-montmorillonite. The particle size D50 of the melamine polyphosphate and phosphate ester oligomers is 3-5 μm. The phosphate oligomer is selected from at least one of bis(4-aminophenyl)-phenyl phosphate, bisphenol A bisphosphate, or resorcinol phosphate oligomer; the silicon-based flame retardant is polysiloxane microspheres.
4. The ultra-thin halogen-free flame-retardant polypropylene material according to claim 1, characterized in that: The compatibilizer includes glycidyl methacrylate-grafted PP, silane coupling agent, and dispersant; based on the total mass of the compatibilizer as 100%, glycidyl methacrylate-grafted PP accounts for 60-70 wt%, silane coupling agent accounts for 12-20 wt%, and dispersant accounts for 15-25 wt%.
5. The ultra-thin halogen-free flame-retardant polypropylene material according to claim 1, characterized in that: The anti-dripping agent comprises polytetrafluoroethylene (PTFE) micro powder and a charring agent; based on 100% of the total mass of the anti-dripping agent, the PTFE micro powder accounts for 40-60 wt%, and the charring agent accounts for 40-60 wt%. The char-forming agent is selected from at least one of pentaerythritol, sorbitol, xylitol, melamine polyol, or starch polyol.
6. The ultra-thin halogen-free flame-retardant polypropylene material according to claim 1, characterized in that: The antioxidants include antioxidant 1010, antioxidant 168, and polysiloxane-coated nano zinc oxide; based on the total mass of antioxidants as 100%, antioxidant 1010 accounts for 35-50 wt%, antioxidant 168 accounts for 35-50 wt%, and polysiloxane-coated nano zinc oxide accounts for 10-20 wt%.
7. A method for preparing an ultrathin halogen-free flame-retardant polypropylene material according to any one of claims 1-6, characterized in that: Includes the following steps: S1. Raw material pretreatment: Each raw material is dried separately to ensure that the moisture content of the raw materials is <0.05%; S2. High-speed mixing: Add each raw material into the high-speed mixer according to the formula and mix evenly; S3. Twin-screw granulation: The material mixed in step S2 is melt-extruded and granulated using a twin-screw extruder. The barrel temperature is controlled at 175-190℃, the screw speed at 250-300rpm, and the feeding speed at 120-140kg / h. Then, the material is water-cooled, pelletized, and dried to obtain flame-retardant PP masterbatch. S4. Melt Plasticization and Molding: The flame-retardant PP masterbatch obtained in step S3 is melt plasticized by an extruder and then melt-molded to obtain an ultra-thin halogen-free flame-retardant polypropylene material.
8. The method for preparing an ultrathin halogen-free flame-retardant polypropylene material according to claim 7, characterized in that: In step S1, the polypropylene resin is vacuum dried at 80°C for 2 hours; the modified intumescent composite halogen-free flame retardant is vacuum dried at 80°C for 3.5–4 hours; and the compatibilizer, antioxidant, anti-dripping agent, and lubricant are dried at 80°C for 2 hours.
9. The method for preparing an ultrathin halogen-free flame-retardant polypropylene material according to claim 7, characterized in that: The preparation method of the modified intumescent composite halogen-free flame retardant includes the following steps: S1. Modification of montmorillonite: Sodium-based montmorillonite is vacuum dried to remove adsorbed water; then the montmorillonite is surface activated with a silane coupling agent ethanol solution, dried, and set aside to obtain modified montmorillonite. S2. Premixed compound: Melamine polyphosphate, phosphate oligomer and silicone flame retardant are premixed evenly according to the weight parts, and then put into a high-speed mixer. The temperature is controlled at 85℃ and the speed is 800rpm. At the same time, modified montmorillonite is added in batches. S3, Intercalation and Delamination: The materials mixed in S2 are subjected to closed kneading treatment at a temperature of 110℃ for 25-35 minutes. By utilizing high-speed shearing and the intercalation effect of silane coupling agent, the interlayer structure of montmorillonite is opened up by flame retardant molecules, achieving single-layer nano-delamination. S4. Cooling and pulverizing: After cooling, the material is pulverized and sieved by airflow to obtain flame retardant-nano montmorillonite composite powder, which is the modified intumescent composite halogen-free flame retardant.
10. The method for preparing an ultrathin halogen-free flame-retardant polypropylene material according to claim 7, characterized in that: In step S3, the length-to-diameter ratio of the twin-screw extruder is L / D = 48:1; the cooling water temperature is 10–40°C; and the moisture content after drying is less than 0.1%. In step S4, the extrusion temperature of the extruder is 200-220°C; the temperature of the molding die for the molding process is 210-225°C, and the cooling temperature is 25-50°C.
Citation Information
Patent Citations
Halogen-free high-flame-retardant high-toughness polypropylene film material and preparation method thereof
CN120059348A
Highly-filled anti-aging flame-retardant polypropylene film and preparation method thereof
CN121249055A